Effect of Tramadol and Pethidine on Shivering during Cesarean Section under Spinal Anaesthesia (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Shivering is a common complication observed in post spinal anaesthesia. Shivering can be very unpleasent and physiologically stressful for the patients. Different drugs are used for prevention and treatment of post spinal shivering.Objective: This study was designed to evaluate the efficacy and side effects of tramadol comparing pethidine in treatment of shivering on pregnant patients during cesarean section under spinal anaesthesia.Methods: This prospective clinical type of study was conducted in the department of Anaesthesia and Intensive Care at Combined Military Hospital, Dhaka from July 2011 to June 2012. One hundred twenty American Society of Anaesthesiologist (ASA) grade I and II pregnant patients of cesarean section under spinal anaesthesia, who had shivering, were included in this study. Patients were divided into two groups. Group T(n=60) received tramadol 0.5mg/kg and Group P(n=60) received pethidine 0.5mg/kg body weight intravenously for treatment of shivering. Grade of shivering, disappearance of shivering and side effects were recorded and subsequently analyzed.Results: Disappearance of shivering after treatment was significantly earlier in Group T (3.09±0.86 minutes) than Group P (5.11±1.08 minutes) (P